1991
DOI: 10.1002/app.1991.070420514
|View full text |Cite
|
Sign up to set email alerts
|

Epoxy–lignin polyblends: Correlation between polymer interaction and curing temperature

Abstract: A bisphenol A-polyamine hardener based epoxy adhesive ( E P ) was modified by polyblending with Kraft lignin ( L ) . EP-L polyblends with an L content up to 40% by weight were cured at room temperature or above their glass transition temperature ( T,) . Previous data have shown that the thermal and viscoelastic properties, as well as adhesive performance of the EP-L polyblends, are influenced by the curing temperature and by the L content in thermally cured polyblends. A reasonable explanation for the differen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
22
0

Year Published

1992
1992
2013
2013

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 45 publications
(22 citation statements)
references
References 15 publications
0
22
0
Order By: Relevance
“…simply blending the liquid EP prepolymer, hardener, and lignin powder at room temperature. Previous data [5,6] have shown an increased adhesive performance of a bisphenol A-polyamine EP adhesive modified by polyblending with kraft lignin. Differential scanning calorimetry (DSC), dynamic mechanical analysis (DMA), and nuclear magnetic resonance (NMR) techniques showed that thermally cured blends with up to 20% lignin are miscible systems.…”
Section: Introductionmentioning
confidence: 88%
See 2 more Smart Citations
“…simply blending the liquid EP prepolymer, hardener, and lignin powder at room temperature. Previous data [5,6] have shown an increased adhesive performance of a bisphenol A-polyamine EP adhesive modified by polyblending with kraft lignin. Differential scanning calorimetry (DSC), dynamic mechanical analysis (DMA), and nuclear magnetic resonance (NMR) techniques showed that thermally cured blends with up to 20% lignin are miscible systems.…”
Section: Introductionmentioning
confidence: 88%
“…The working procedure has been described in previous work [5]. The molecular weight distributions of the unfractionated TO and its three fractions were obtained by GPC (Fig.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Because of the less complex chemistry, simple direct polymer blend with lignin, epoxy group-containing chemicals and curing agents, for example, amine containing reagents -were commonly studied. [161][162][163][164][165][166][167][168] Lignin-based epoxy resin mostly investigated its thermal properties, mechanical properties and morphological characters with scanning electron microscopy (SEM).…”
Section: Phenol Epoxymentioning
confidence: 99%
“…Functionalization of lignin by hydroxyalkylation or phenolation, followed by reaction with epichlorohydrin, allowed epoxy-functional lignins to be obtained, which may be cured with diamines or anhydrides [95,115,116].…”
Section: Lignin In Thermosetsmentioning
confidence: 99%